2009
DOI: 10.1021/bi900308c
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Interaction of a Single G-Protein Key Binding Site with Rhodopsin Disk Membranes upon Light Activation

Abstract: Heterotrimeric G-proteins interact with their G-protein-coupled receptors (GPCRs) via key binding elements comprising the receptor-specific C-terminal segment of the alpha-subunit and the lipid anchors at the alpha-subunit N-terminus and the gamma-subunit C-terminus. Direct information about diffusion and interaction of GPCRs and their G-proteins is mandatory for an understanding of the signal transduction mechanism. By using single-particle tracking, we show that the encounters of the alpha-subunit C-terminus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…The existence of such precomplexes has been suggested by others (21,37,(64)(65)(66)(67)(68)(69). Here, we found that the existence of precomplexes is consistent with our kinetic data if they are sufficiently transient.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The existence of such precomplexes has been suggested by others (21,37,(64)(65)(66)(67)(68)(69). Here, we found that the existence of precomplexes is consistent with our kinetic data if they are sufficiently transient.…”
Section: Resultssupporting
confidence: 93%
“…1)). Evidence for the existence of such precomplexes has been reported in several studies (21,37,(64)(65)(66)(67)(68)(69), and it has been hypothesized that they are beneficial for G activation (37). Analogous to the formation of the reactive complex R Ã þ G#R Ã G (Eqs.…”
Section: Existence Of Rg Precomplexesmentioning
confidence: 94%
“…To investigate the consequences of a track structure on reaction kinetics, the encounter rate of G t with rhodopsin and the kinetics of G t activation were simulated for three different structural scenarios ( Figure 5B): (i) rhodopsin and G t are free to diffuse according to the classic collision-coupling model of signaling by random encounters of molecules (control); (ii) immobile rhodopsin is organized in tracks; light activates rhodopsin (R*) either on the outside or inside of a track; and (iii) rhodopsin and G t form a precomplex RG t , with a kinetic stability that is determined by on and off rate constants. Although preassembly has yet to be demonstrated in vivo, at least simulations and studies using solubilized and reconstituted rhodopsin and G t suggest preassembly of signaling components (Alves et al, 2005;Dell'Orco and Koch, 2011;Fanelli and Dell'orco, 2008;Kim et al, 2009).…”
Section: Simulation Of Transducin Activation Kinetics By Different Rhmentioning
confidence: 99%
“…Preassembly of G t has been studied in vitro using solubilized rhodopsin and G t molecules (Alves et al, 2005;Dell'Orco and Koch, 2011;Fanelli and Dell'orco, 2008;Kim et al, 2009). However, high-affinity sites for preassembly might involve several rhodopsin molecules in a track and might require G t tethered to the disk membrane via its isoprenyl modification.…”
Section: Molecule Preassembly On Tracks Does Not Slow Down Activationmentioning
confidence: 99%
“…Examples are fluorescent dyes such Atto647N, which can be excited at 640 nm where the amount of rhodopsin absorption is negligible [74]. Another approach is to constantly introduce new sample into the measuring beam.…”
Section: Challenges In Performing Fluorescence Experiments With Rementioning
confidence: 99%